INOVASI PENDAMPING SEKOLAH LAPANG UNTUK DESA INKLUSIF - Asmiyanto, Tri; Sugiyanto, Sugiyanto (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
This study examines the role of innovation and facilitation strategies in overcoming multidimensional challenges to implement the No One Left Behind (NOLB) principle at the village level through the School of Inclusive Village program. The study was conducted in the villages of Ngipak and Petir in the Gunungkidul Regency, which have contrasting social and geographical characteristics. Petir faces structural poverty, with many tenant farmers and families experiencing psychosocial issues. Ngipak, on the other hand, has a high proportion of elderly individuals and single mothers, but limited data on vulnerable groups. A qualitative case study approach was used to collect data through in-depth interviews, participatory observation, and document review. The data were analyzed using the Miles and Huberman interactive model. The study's results show that mentors play a role that extends beyond administrative functions. They act as grassroots agents of change, promoting inclusive innovations based on local knowledge and cultural practices. These innovations include administrative (simplifying procedures for vulnerable groups), social (forming a disability forum), pedagogical (practice-based learning), economic (strengthening family businesses for psychosocially vulnerable families), and institutional (forming a school field management committee through a Head of Village decision). The empowerment strategy is relational, adaptive, and transformative, emphasizing trust-building, safe participatory spaces, cross-sectoral collaboration, and promoting inclusion values in village governance. However, the mentors addressed structural challenges (limited flexible funding and weak institutional support), cultural challenges (social exclusion and stigma), and technical challenges (limited digital access and infrastructure). This study concludes that inclusive village development requires continuous social facilitation, a humanistic approach, and systemic support. The School of Inclusive Village Mentors successfully implemented the No One Left Behind principle, turning it into meaningful action at the village level. ABSTRAKPenelitian ini mengkaji peran inovasi, strategi fasilitasi, dan tantangan multidimensi pendamping Sekolah Lapang Desa Inklusif (SLDI) dalam mendorong penerapan prinsip No One Left Behind (NOLB) di tingkat desa. Studi ini dilakukan di Kalurahan Ngipak dan Petir, Kabupaten Gunungkidul, yang memiliki karakteristik sosial-geografis kontras; Kalurahan Petir menghadapi kemiskinan struktural dengan dominasi petani penggarap dan banyak keluarga ODGJ, sedangkan Kalurahan Ngipak memiliki proporsi tinggi lanjut usia dan perempuan kepala keluarga dengan tantangan data kelompok rentan yang terbatas. Menggunakan pendekatan studi kasus kualitatif, data dikumpulkan melalui wawancara mendalam, observasi partisipatif, dan telaah dokumen, kemudian dianalisis dengan model interaktif Miles dan Huberman. Hasil penelitian menunjukkan pendamping menjalankan peran melampaui fungsi administratif; mereka bertindak sebagai agen perubahan akar rumput dengan inovasi inklusif berbasis pengetahuan lokal dan praktik budaya. Inovasi tersebut meliputi dimensi administratif (penyederhanaan prosedur kelompok rentan), sosial (pembentukan forum disabilitas), pedagogis (pembelajaran berbasis praktik lokal), ekonomi (penguatan usaha keluarga ODGJ), dan kelembagaan (pembentukan pengurus sekolah lapang melalui SK Lurah). Strategi pemberdayaan bersifat relasional, adaptif, dan transformatif, tekanan pembangunan kepercayaan, ruang aman partisipatif, kolaborasi lintas sektor, serta pengarusutamaan nilai inklusi dalam tata kelola desa. Namun, pendamping menangani tantangan struktural (minimnya dana fleksibel, lemahnya dukungan kelembagaan), kultural (stigma eksklusi sosial), dan teknis (akses digital, keterbatasan data dan infrastruktur). Penelitian ini menyimpulkan bahwa pembangunan desa inklusi memerlukan fasilitasi sosial berkelanjutan, pendekatan humanistik, dan dukungan sistemik, di mana pendamping SLDI berhasil menerjemahkan prinsip NOLB dari wacana menjadi tindakan nyata dan bermakna pada tingkat desa.